Physiological indicators of stress in gestating sows under different cooling systems - Quiñonero, Jose; García-Santamaría, Carlos; María-Dolores, Emilio; Armero, Eva (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine physiological stress markers, neutrophil:lymphocyte ratio (N/L) and corticoid concentrations, in gestating sows under different cooling systems. A sprinkling cooling system (SS) and a system based on fan-assisted evaporative cellulose pad (PS) were used. SS showed higher N/L ratio (1.095) than PS (0.850). Corticoid concentrations showed high variability. Corticosteroids are more efficient short-term stress indicators while N/L ratio is a good medium and long-term stress indicator. According to N/L ratio, gestating sows under PS benefit from a higher level of welfare.